Ultra low power EMG amplifier - Gibran, Limi Jaya. (2009)
In this project, the writer was able to design two low power amplifiers dedicated to EMG signal pre-amplification and explore a novel power reduction technique for switched capacitor circuits. The amplifiers were designed under a supply voltage of ±0.9V. The technology used to realize the amplifiers is CSM 0.18um CMOS technology. Both of the amplifiers have identical design (both are sample and hold switched capacitor gain circuit) but the later one employs the novel power reduction technique.